2019
DOI: 10.1111/apa.14791
|View full text |Cite
|
Sign up to set email alerts
|

Early‐life exposure to common virus infections did not differ between coeliac disease patients and controls

Abstract: Aim Our aim was to compare the presence of various common viruses (rhinovirus, enterovirus, adenovirus, Epstein–Barr virus, cytomegalovirus, norovirus, parechovirus) in stool and nasal swab samples as well as virus‐specific antibodies in serum samples between children who developed coeliac disease and controls. Methods A case–control study was established based on the DIABIMMUNE Study cohorts. During the study, eight Estonian children and 21 Finnish children aged 1.5 years to five years developed coeliac disea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 31 publications
1
10
0
1
Order By: Relevance
“…In addition, enteroviruses have previously been detected in the small bowel mucosa of coeliac disease patients 26. Moreover, enteroviral infections prior to 1 year of age were not associated with increased risk of coeliac disease, while those occurring after the age of 1 year increased the risk 12 27. Our findings are consistent with both of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, enteroviruses have previously been detected in the small bowel mucosa of coeliac disease patients 26. Moreover, enteroviral infections prior to 1 year of age were not associated with increased risk of coeliac disease, while those occurring after the age of 1 year increased the risk 12 27. Our findings are consistent with both of these previous studies.…”
Section: Discussionsupporting
confidence: 92%
“…One small prior study investigating parechovirus and CD did not detect any parechovirus measured in stool at 3 and 6 months of age. [35] In our data, parechovirus prevalence was very low in this age-group (e.g. 1.0% at ≤4 months of age) which would limit statistical power for analyses restricted to this age-group.…”
Section: Comparison With Other Studiesmentioning
confidence: 54%
“…In cross‐sectional studies investigating enterovirus in duodenal biopsies by RT‐PCR, in situ hybridisation and immunohistochemistry, one study found neither cases with CD nor controls to be positive 46 whereas another study found slightly higher frequencies in cases with CD compared to controls (Table 2). 47 Furthermore, neither cases nor controls had enterovirus in nasal/stool swabs restricted to the first 6 months of life, and antibodies against enterovirus at diagnosis did not differ between cases and matched controls 48 . These findings are not surprising because enterovirus infections are uncommon in early infancy but nearly ubiquitous before the age of three.…”
Section: Specific Microbesmentioning
confidence: 92%
“…After seasonal or pandemic influenza an increased risk of a new diagnosis of CD was found in a nation‐wide register‐based study (HR 1.29 (95% CI, 1.21‐1.38) 63 . In a prospective matched case‐control study with PCR of nasal swabs collected at 3‐6 months, rhinovirus was found in 5/18 children with CD (28%) compared to 0/16 in controls ( P = 0.05) 48 …”
Section: Specific Microbesmentioning
confidence: 98%